Prevalence of kidney stones based on metabolic health and weight criteria: reports from the national health and nutrition examination survey 2007-2018 data analysis - Ding, Xijie; Du, Qingchen; Li, Jianxing; Ji, Chaoyue; Zhang, Endi; Hu, Weiguo (Frontiers in Physiology, 2025)
ObjectiveUsing data from the NHANES collected between 2007-2018, this study aimed to investigate the relationship between the prevalence of kidney stones and metabolically healthy obesity (MHO) and measure the effect of physical activity as a modifying factor.MethodsThis cross-sectional analysis included 12,498 participants aged ≥20 years who were categorized into six groups based on their metabolic status (healthy or unhealthy) and BMI (normal, overweight, and obesity). Kidney stone history was self-reported. Weighted logistic regression models, adjusted for demographic characteristics, comorbidities, and lifestyle variables, were applied to calculate odds ratios and 95% confidence intervals. Subgroup analyses were conducted based on the degree of physical activity.ResultsThe overall prevalence of kidney stones was 10.20%. Participants with metabolically unhealthy obesity (MUO) had the highest prevalence of kidney stones (14.5%), followed by individuals with MHO (11.1%). After full adjustment, compared to participants with MHN, the MHO and MUO groups exhibited significantly greater risks of kidney stones (MHO: OR = 2.10, 95% CI:1.47–2.98, P < 0.001; MUO: OR = 1.98, 95% CI:1.45–2.67, P < 0.001). Physical activity was associated with a decreased risk of kidney stones, particularly among individuals with MUO. Stratified analyses revealed no significant interaction effects by age, sex, or race.ConclusionObesity, irrespective of metabolic health status, was significantly associated with a higher prevalence of kidney stones. Higher levels of physical activity were correlated with lower risks of kidney stones, particularly in metabolically unhealthy individuals. These results underscore the importance of managing body weight and maintaining physical activity as key strategies to prevent kidney stones.